INFLUENCE GEOMETRIC PARAMETER SAWS ON HIS(ITS) CAPACITY TO WORK - Imomkulov SHuhratzhon Boqizhonovich; Abdukahhorov Zohidzhon (Galaxy International Interdisciplinary Research Journal, 2021)
At present is absent the scientific motivation geometric parameter separating saws and rates to accuracy functional parameter. The Question to optimization geometric parameter saws is important and in this connection requires the immediate permit. In article is considered questions bound change of power acting worker of the surfaces teeth saw depending on designs